PSYCHOLOGY OF RAPID SOFTWARE DEVELOPMENT – 2010 - Kondratyev, Y. (Journal of Information Technologies in Education (ITE), 2010)
The article briefs the experience in developing software systems in several areas (physics, trading, telecom) in 1999-2010. The systems are developed by workgroups for private customers and small enterprises. This segment of the market offers young developers to fulfill their individual propensities out of any corporate control. From other side, the article highlights the necessity of preserving and reproducing the CIS IT community, which, traditionally, is on the very high professional level.